Design Guide for Hybrid-Additive Manufacturing of Inconel 718 Combining PBF-LB/M and In Situ High-Speed Milling - David Sommer; Simon Hornung; Cemal Esen; Ralf Hellmann (Journal of Manufacturing and Materials Processing)
As the correlation between design rules and process limitations is of the upmost importance for the full exploitation of any manufacturing technology, we report a design guide for hybrid-additive manufacturing of Inconel 718. Basic limitations need to be evaluated for this particular hybrid approach that combines laser powder bed fusion (PBF-LB/M) and in situ high-speed milling. Fundamental geometric limitations are examined with regard to the minimum feasible wall thickness, cylinders, overhanging structures, and chamfers. Furthermore, geometrical restrictions due to the integrated three-axis milling process with respect to inclinations, inner angles, notches, and boreholes are investigated. From these findings, we derive design guidelines for a reliable build process using this hybrid manufacturing. Additionally, a design guideline for the hybrid-additive manufacturing approach is presented, depicting a step-to-step guide for the adjustment of constructions. To demonstrate this, a powder nozzle for a direct energy deposition (DED-LB/M) process is redesigned following the previously defined guidelines. This redesign encompasses analysis of the existing component and identification of problematic areas such as flat angles, leading to a new construction that is suitable for a hybrid-additive manufacturing approach.